2005
DOI: 10.1074/jbc.m409863200
|View full text |Cite
|
Sign up to set email alerts
|

Role of Tyrosine 441 of Interferon-γ Receptor Subunit 1 in SOCS-1-mediated Attenuation of STAT1 Activation

Abstract: Suppressor of cytokine signaling (SOCS)-1, the key negative regulator of interferon (IFN)-␥-dependent signaling, is induced in response to IFN␥. SOCS-1 binds to and inhibits the IFN␥ receptor-associated kinase Janusactivated kinase (JAK) 2 and inhibits its function in vitro, but the mechanism by which SOCS-1 inhibits IFN␥-dependent signaling in vivo is not clear. Upon stimulation, mouse IFN␥ receptor subunit 1 (IFNGR1) is phosphorylated on several cytoplasmic tyrosine residues, and Tyr 419 is required for sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 53 publications
1
47
1
Order By: Relevance
“…Furthermore, when Tyr-457 is mutated, the resulting receptor is still capable of tyrosine phosphorylation of Jak1, Jak2, and Tyr-479 of IFN-γR1, which creates an evolutionarily conserved (Figure 3) recruitment site for SOCS-1 [48]. All except the last activity are known to require the presence and/or activity of Jak kinases [22,46].…”
Section: Determinants In the Extracellular Domains Differentially Medmentioning
confidence: 99%
“…Furthermore, when Tyr-457 is mutated, the resulting receptor is still capable of tyrosine phosphorylation of Jak1, Jak2, and Tyr-479 of IFN-γR1, which creates an evolutionarily conserved (Figure 3) recruitment site for SOCS-1 [48]. All except the last activity are known to require the presence and/or activity of Jak kinases [22,46].…”
Section: Determinants In the Extracellular Domains Differentially Medmentioning
confidence: 99%
“…Among these genes is SOCS-1 [11,17,18]. SOCS-1 binds to IFN-γR1 and the activation loop of Jak2 (and possibly also Jak1) and prevents either the recruitment of additional Stat proteins or the phosphorylation of target proteins by the Jak kinases [8,19]; thus SOCS-1 can repress signaling by not only IFN-γ but by other cytokines using the Jak/Stat pathway. Another notable gene induced by Stat1 is IRF-1, whose induction is necessary for the upregulation of MHC Class I and Class II [20,21], FasL [22], and caspases-1 and -8 [23,24] by IFN-γ.…”
Section: Modulation Of Stat1 Activation By the Ifn-γ Receptor 114mentioning
confidence: 99%
“…The interaction of IFN-γ with this integral membrane receptor complex results in structural rearrangements in the receptor complex and the activation of Jak1 and Jak2 tyrosine kinases bound to the intracellular domains of IFN-γR1 and IFN-γR2 respectively [4][5][6]. Activation of Jak kinases results in the tyrosine phosphorylation of Jak1 and Jak2 on their kinase domains, and of the COOH-terminus of IFN-γR1 in two locations, which allow the recruitment of latent Stat1 and SOCS-1 [4, [7][8]. Translocation of Stat1 to the nucleus allows Stat1 to modify the transcription of a fraction of IFN-γ-sensitive genes [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, SOCS1 was initially recognized as a repressor factor of IFN-γ, which is a critical molecule involved in the initiation of inflammation and is required for normal postnatal growth and survival (4)(5)(6). Knockout studies in mice suggest the role of SOCS1 as a modulator of IFN-γ action (7). Further studies have shown that SOCS1 can be induced by the activated janus kinase family (JAK) and the signaling transduction and activators of transcription family (STATs), and may downregulate the JAK/Stats signaling pathway (8), which plays an important role in the initiation and activation of inflammation, through inhibition of the phosphorylation of kinase mentioned above.…”
Section: Introductionmentioning
confidence: 99%